Performance goals in public management and policy the nature and implications of goal ambiguity - Jung, Chan Su ([Edward Elgar], 2018)
Chan Su Jung provides a thorough review of goal ambiguity in the public sector, exploring the general assertions, arguments and empirical evidence regarding performance goal ambiguity, particularly highlighting its causes, consequences, and mediation effects. The author proposes a new conceptual framework for successful analysis of goal ambiguity that can effectively relate to diverse organizational and program characteristics.